Design of a Web Tracer Study Application and Alumni Data Management at the Faculty of Sharia and Law - Riansyah, Rusma; Syahputra, Alwi (Journal of Computer Science and Informatics Engineering, 2025)
This research aims to design a web-based tracer study application and alumni data management system at the Faculty of Sharia and Law UINSU using the Waterfall method with a Model-View-Controller (MVC) approach. The system was developed using PHP 8.0, MySQL 8.0, HTML5, and CSS3 technologies. Functional testing shows 100% success on all features, usability evaluation using System Usability Scale (SUS) resulted in an average score of 82 (Excellent category), and performance testing shows login response time of 1.5 seconds with stability at 25 simultaneous users. User Acceptance Test shows 100% of users stated the system is easy to use. Implementation resulted in an alumni response rate of 78.6%, with 64.4% of alumni working in the legal sector and 75.4% stating that lecture competencies match work requirements. Innovative features include automatic email reminders, LinkedIn integration, dynamic visualization, and automatic password reset. The system has proven effective in improving the efficiency of alumni data collection from manual to digital and supporting data-based accreditation processes and curriculum evaluation